Traffic- Croatia Facing the Global Issues - Ivan Mahalec; Zoran Lulić; Ivan Mavrin (Promet - Traffic&Transportation, 1970)
Traffic today is an indispensable part of our lives and oneof the basic preconditions of what is called social progress. Likeblood in our body it circulates across the whole globe and allowsfor the necessary flow of people and materials. This workconsiders the impact of traffic on the lives of people and on theenvironment, analyses the available energy sources and vehiclepropulsion systems and illustrates global climatic issues. Thepaper presents the methodology created by EU for monitoringof harmful emissions at the national/eve! and gives data on differencesin emissions of individualtransp01t modes. The trafficcondition in the Republic of Croatia is analysed and a thesis isgiven regarding possible solution of the stated problems.